ANALYSIS OF THE EFFECT OF SOCIAL MEDIA AND EXPERIENTIAL MARKETING ON CONSUMER PURCHASE DECISIONS OF RAINBOW RICE MEDAN - Sylvia Sari, Asri; Arto Pujangkoro, Sugih; Karina Fawzeea Sembiring, Beby (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The culinary business is currently a business that has the potential to grow quite rapidly. That way the businessmen must have more efforts to maintain the existence of their culinary business. In this case, social media plays an important role in the media that conveys information ranging from promotions to what products or menus are sold by the businessman. The location of this research was carried out at Rainbow Rice Medan on Jalan Captain Muslim, Megapark Komplek Megacomm. Population is a generalization area consisting of objects/subjects that have certain qualities and characteristics determined by researchers to study and then draw conclusions. The population in this study are consumers who have already purchased products from Rainbow Rice Medan. The number of samples in this study is unknown. The influence of Social Media variables on Purchase Decisions with a coefficient value of 1.101, a P-Values value of 0.000 0.05 and a T statistics value of 9.985 1.661 (significant). The F-Square value is 1.063. The influence of the sense of the Panca Indra variable on purchasing decisions with a path coefficient value of -0,302, a P-Values value of 0.032 0.05 and a T statistics value of 2.145 1.661 (significant). The F-Square value is 0.091. The effect of the Feeling variable on the Purchase Decision with the path coefficient value of 0.140, the P-Values value of 0.465 0.05 and the T statistics value of 0.730 1.661 (not significant). F-Square of 0.008. The influence of the Thinking variable on the Purchase Decision with the path coefficient value of 0.137, the P-Values value of 0.569 0.05 and the T statistics value of 0.570 1.661 (not significant). F-Square of 0.006. The influence of the Action variable on the Purchase Decision with the path coefficient value of -0.399, the P-Values value of 0.066 0.05 and the T statistics value of 1.839 1.661 (no significant effect). F-Square of 0.087. The influence of the relationship variable on purchasing decisions with a path coefficient value of 0.178, a P-Values value of 0.275 0.05 and a T statistics value of 1.093 1.661 (not significant). F-Square of 0.022. Stimulant Effect on Purchasing Decisions There is a simultaneous positive and significant effect of all independent variables on the dependent variable with an R-Square value of 0.836, a P-Values value of 0.000 0.05 and a T Statistics value of 25,752 1.661 (significant). It can be concluded that the Raibow Rice Medan is known by the public through social media such as Instagram.